A COMPARATIVE STUDY OF PERSONALITY TRAITS OF CRICKET AND SOFTBALL INTER-COLLEGIATE PLAYERS - Shirsath, Shekhar N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the present study was to assess the personality traits of Cricket and Softball Inter-Collegiate men players of Dr. Babasaheb Ambedkar Marathwada University. The study conducted on fifty samples, consisting of twenty five Cricket and twenty five Softball Inter-Collegiate men players of Dr. Babaheb Ambedkar Marathwada University. Personality traits were obtained by administrating R. B. Cattell’s Sixteen Personality Factor questionnaire. The data collected through this test were analyzed with respect to second order personality traits i.e. dependence, control and adjustment. T test was applied to compute the significance of differences among two groups. The significance of data was judged at 05 levels. The result of the study indicates that personality traits of Cricket and Softball Inter-Collegiate men players are same.